Pharmacologic treatment of GERD: Where we are now, and where are we going?. Issue 1 (15th September 2020) - Scarpignato, Carmelo; Hongo, Michio; Wu, Justin C. Y.; Lottrup, Christian; Lazarescu, Adriana; Stein, Ellen; Hunt, Richard H.
Abstract: The introduction of acid inhibition in clinical practice has revolutionized the management of acid‐related diseases, leading to the virtual abolition of elective surgery for ulcer disease and relegating antireflux surgery to patients with gastroesophageal reflux disease (GERD) not adequately managed by medical therapy. Proton pump inhibitors (PPIs) are the antisecretory drugs of choice for the treatment of reflux disease. However, these drugs still leave some unmet clinical needs in GERD. PPI‐refractoriness is common, and persistent symptoms are observed in up to 40–55% of daily PPI users. Potassium‐competitive acid blockers (P‐CABs) clearly overcome many of the drawbacks and limitations of PPIs, achieving rapid, potent, and prolonged acid suppression, offering the opportunity to address many of the unmet needs. In recent years, it has been increasingly recognized that impaired mucosal integrity is involved in the pathogenesis of GERD. As a consequence, esophageal mucosal protection has emerged as a new, promising therapeutic avenue. When P‐CABS are used as add‐on medications to standard treatment, a growing body of evidence suggests a significant additional benefit, especially in the relief of symptoms not responding to PPI therapy. On the contrary, reflux inhibitors are considered a promise unfulfilled, and prokinetic agents should only be used on a case‐by‐case basis. Abstract : In recent years, it has been increasingly recognized that impaired mucosal integrity is involved in the pathogenesis of GERD. As a consequence, esophageal mucosal protection has emerged as a new, promising therapeutic avenue. Some compounds affecting esophageal mucosal integrity exist, but the majority of currently available formulations are ineffective. A recently introduced mucoadhesive formulation, containing two natural polysaccharides, proved to be effective in both erosive and nonerosive reflux disease, where it also increased the response rate to PPIs. On the contrary, reflux inhibitors are today considered a promise unfulfilled, and prokinetic agents should only be used on a case‐by‐case basis.